DRUGS OF MAMMALIAN ORIGIN USED BY THE TRIBALS OF BIHAR PART -I - AZMI, H. KHALID; FATIMA, KAYNAT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
During the course of medico-ethnozoological survey of Bihar, covering 15 districts, available information with regard to the native use of medicinal mammals by the tribals in the treatment of human diseases have been recorded. The study has revealed, the use of 12 mammalian species in the treatment of various human ailments.